Sebuah Ilmu Menghasrat: Topografi Studi Spiritualitas di Indonesia - Nindyo Sasongko; Febrianto (Indonesian Journal of Theology, 2021)
This is an editorial introduction to the Special Issue "Desiring Love: Foundations of Spirituality."